2019
DOI: 10.3389/fphys.2019.00314
|View full text |Cite
|
Sign up to set email alerts
|

In silico Characterization of Human Prion-Like Proteins: Beyond Neurological Diseases

Abstract: Prion-like behavior has been in the spotlight since it was first associated with the onset of mammalian neurodegenerative diseases. However, a growing body of evidence suggests that this mechanism could be behind the regulation of processes such as transcription and translation in multiple species. Here, we perform a stringent computational survey to identify prion-like proteins in the human proteome. We detected 242 candidate polypeptides and computationally assessed their function, protein–protein interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 95 publications
4
17
0
2
Order By: Relevance
“…In algae, these amyloidogenic prion-like proteins may enable bio lm formation as determinants of high mechanical resistance of exo-polysaccharides [35], also seen in bacteria [36], supported further by the fact that we found all four chlorophytes in this study, enriched in signalling-related genes especially, mitogen-activated protein kinases (MAPK), protein kinases, and response regulators. A consensus on overrepresentation of nucleic acid binding functions among the amyloid-forming proteins exists already, and is a common characteristic of PrLPs (Silva and Cordeiro, 2016;Iglesias et al, 2019), and this too, is further corroborated by our results that indicate 40% of PrLPs to have RNA and DNA binding functions in the plant prionomes.…”
Section: Discussionsupporting
confidence: 86%
“…In algae, these amyloidogenic prion-like proteins may enable bio lm formation as determinants of high mechanical resistance of exo-polysaccharides [35], also seen in bacteria [36], supported further by the fact that we found all four chlorophytes in this study, enriched in signalling-related genes especially, mitogen-activated protein kinases (MAPK), protein kinases, and response regulators. A consensus on overrepresentation of nucleic acid binding functions among the amyloid-forming proteins exists already, and is a common characteristic of PrLPs (Silva and Cordeiro, 2016;Iglesias et al, 2019), and this too, is further corroborated by our results that indicate 40% of PrLPs to have RNA and DNA binding functions in the plant prionomes.…”
Section: Discussionsupporting
confidence: 86%
“…In algae, these amyloidogenic prion-like proteins may enable biofilm formation as determinants of high mechanical resistance of exo-polysaccharides (Mostaert et al, 2009), also seen in bacteria (Romero et al, 2010), supported further by the fact that we found all four chlorophytes in this study, enriched in signallingrelated genes especially, mitogen-activated protein kinases (MAPK), protein kinases, and response regulators. A consensus on overrepresentation of nucleic acid binding functions among the amyloid-forming proteins exists already, and is a common characteristic of PrLPs (Silva and Cordeiro, 2016;Iglesias et al, 2019), and this too, is further corroborated by our results that indicate 40% of PrLPs to have RNA and DNA binding functions in the plant prionomes.…”
Section: Discussionsupporting
confidence: 86%
“…A significant fraction of proteins involved in transcriptional regulation both in yeast and mammalian cells contain sequences, enriched by Q and/or N residues that are similar to prion domains (PrDs) of yeast prions [ 31 , 32 , 33 ] and therefore termed PrD-like domains (PrDL). However, the abilities of the majority of these proteins to form an amyloid and their potential role as amyloids are not studied.…”
Section: Introductionmentioning
confidence: 99%